Zirconium normalized trace element data of the Smoky Hollow (SH#1) core in south central Utah - Victoria Fortiz; Rosie L Oakes; F Garrett Boudinot; Matthew M Jones; R Mark Leckie; Bradley B Sageman; Julio Sepúlveda; Timothy J Bralower (PANGAEA, 2021)
Trace element data from the Smoky Hollow #1 core drilled across the Cenomanian-Turonian boundary near Big Water, south-central Utah in 2014. Ground bulk samples were analyzed via Laser Ablation Inductively Coupled Plasma Mass Spectrometry (LA-ICP-MS) in the Laboratory for Isotopes and Metals in the Environment (LIME) at The Pennsylvania State University. Results are given with both raw (bulk) and normalized to Zr to correct for detrital input.
In: Fortiz, V et al. (2021): Trace element and calcareous nannofossil assemblage of the Smoky Hollow (SH#1) core in south central Utah [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.938507